The Year of the Garden - Book 5 - Cheng, Andrea; Barton, Patrice, 1955- (Boston, 2017)
"Follows perceptive, astute Anna as she strives to grow a perfect garden -- only to realize that the garden she grows with her new friend is more than good enough, weeds and all"--Provided by publisher.
Keywords: Chinese Americans -- Juvenile fiction; Friendship -- Juvenile fiction; Gardening -- Juvenile fiction; Moving, Household -- Juvenile fiction; Juvenile fiction